Performance Investigation Of Photovoltaic Grid Connection For Shunt Active Power Filter With Different PWM Generation - Ibrahim, Zulkifilie; Abu Hasim, Ahmad Shukri; Talib, Md Hairul Nizam; Mat Lazi, Jurifa; Mat Isa, Siti Noormiza; Mstafa, Raihana (Little Lion Scientific Islamabad Pakistan, 2013)
-